The Influence of principals’ Instructional Leadership on teachers’ Professional Learning Community: the mediating role of school climate - Hua, Shihui; Mansor , Azlin Norhaini; Bin Jamaludin, Khairul Azhar; Chen, Xin (Salud, Ciencia y Tecnología - Serie de Conferencias, 2024)
Effective management has a big effect on teachers’ professional development and the establishment of mutual learning environments. The outcome of Principals’ Instructional Leadership (PTL) on the growth of primary school teachers’ professional learning communities was examined in this research, with a focus on the mediating function of school climate, particularly behaviors related to trust and knowledge sharing. 750 teachers from 85 primary schools, from a diversity of socioeconomic backgrounds throughout five districts, participated in the survey. The development of teachers’ professional learning communities and principals’ teaching leadership were found to be significantly correlated by the study using correlation analysis, mediation analysis, and structural equation modeling (SEM). Principals’ leadership in developing a learning-centered atmosphere directly affected teachers’ involvement and professional learning; this effect was entirely mediated by the degree of trust and information exchange in the school environment. According to these findings, principals can create a supportive school climate that promotes professional development by emphasizing teachers’ collaborative knowledge sharing and trust building to strengthen professional learning communities.